2016
DOI: 10.1177/0300060515621445
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the clinical effectiveness of 3D and 2D imaging systems for laparoscopic radical cystectomy with pelvic lymph node dissection

Abstract: ObjectiveTo compare the clinical effectiveness of three-dimensional (3D) and two-dimensional (2D) laparoscopic imaging systems for radical cystectomy (RC) with pelvic lymph node dissection.MethodsThis was a retrospective analysis of data collected from all patients who underwent RC with pelvic lymph node dissection between January 2013 and May 2014, performed by a single surgeon in our clinic. Demographic characteristics and operative data from the procedure were collected and compared.ResultsData were availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…For the operator, there was also reduced stress in the upper arms and eyes and a lower risk of headaches [3]. Similar results were reported for cystectomy, with reduced operative times due to the increased definition of tissues [6]. It therefore appears that 3D laparoscopy could gradually replace 2D techniques in urological surgery.…”
Section: Discussionsupporting
confidence: 52%
“…For the operator, there was also reduced stress in the upper arms and eyes and a lower risk of headaches [3]. Similar results were reported for cystectomy, with reduced operative times due to the increased definition of tissues [6]. It therefore appears that 3D laparoscopy could gradually replace 2D techniques in urological surgery.…”
Section: Discussionsupporting
confidence: 52%
“…Author's name, publication year, study design, study characteristics, and quality assessment of all the studies are summarized in Table 1 . Of these, four studies 17 , 20 , 23 , 27 were excluded from the meta-analysis (one adrenalectomy study, one ureterolithotomy study, and one cystectomy study were excluded because there were no similar studies to compare with since we designed our study to compare studies addressing similar procedures, and the fourth study about pyeloplasty was excluded due to lack of a standard deviation parameter for meta-analysis comparison). The remaining 13 studies (3 randomized and 10 observational) containing 548 patients operated on with a 2D laparoscopic system and 449 patients operated on with a 3D laparoscopic system were divided into three groups according to surgical type.…”
Section: Resultsmentioning
confidence: 99%
“… 38 However, other investigators failed to find any significant difference between 2D and 3D laparoscopic surgeries concerning total surgical expenses. 27 , 28 On the other hand, discomfort, nausea, dizziness, and eye strains are among the reported limitations associated with the old generation of the 3D laparoscopic system. 39 However, the new 3D high-definition generations did not show any of the above limitations compared with the 2D laparoscopic system.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, our results showed that compared with 2D endoscopic displays, 3D endoscopic displays have advantages in terms of LNDs. Feng et al [ 44 ] also reported that 3D stereoscopic imaging reduced both the duration of lymph node dissection and the overall operative time during laparoscopic radical cystectomy with pelvic lymph node dissection. 3D laparoscopic visualization and the associated better image quality play a decisive role in distinguishing anatomical structures, which may be beneficial for dissecting lymph nodes and more complicated surgeries.…”
Section: Discussionmentioning
confidence: 99%